Parenting Stress and Child Behavior Problems: A Transactional Relationship Across Time - Neece, Cameron L. (Am J Intellect Dev Disabil, 2012)
Parenting stress and child behavior problems have been posited to have a transactional effect on each other across development. However, few studies have tested this model empirically. The authors investigated the relationship between parenting stress and child behavior problems from ages 3 to 9 years old among 237 children, 144 of whom were typically developing and 93 who were identified as developmentally delayed. Behavior problems and parenting stress covaried significantly across time for both groups of children. Cross-lagged panel analyses generally supported a bidirectional relationship between parenting stress and child behavior problems for mothers and fathers.